Analisis Faktor Yang Mempengaruhi Berpikir Kritis Matematika Siswa Dalam Proses Pembelajaran Daring Selama Pandemi - Dina Rahayu Batubara; Age Alifya; Tua Halomoan Harahap (Journal Mathematics Education Sigma [JMES], 2022)
Abstract. The COVID-19 pandemic which has spread throughout the world in early 2020 has had an impact on teaching and learning activities in schools. The Ministry of Education and Culture as well as several regional officials issued a policy in the form of changing teaching and learning activities carried out online (online). This study aims to find out how many factors influence students' critical thinking in mathematics in the online learning process during the covid-19 pandemic and to determine the factors that significantly affect students' critical thinking in a total of 20 statements. The population in this study were high school students at Tabib Tabanan Jl. Bunga Kardiol Ladang Bambu and the number of samples was 29 students. The instrument in this study was in the form of a questionnaire or questionnaire. The results of this study found that the analysis of students' critical thinking in mathematics in the online learning process during the COVID-19 pandemic had a positive effect. In the reliability test, physical condition has a value of 0.679%, meaning that the indicator of physical condition affects critical thinking by 67.9% and anxiety has a value of 0.675%, meaning that the indicator of anxiety affects critical thinking. So it can be concluded that the factor that influences students' critical thinking in learning mathematics is the factor that has the highest score is the physical condition factor. So it is necessary for students to continue to maintain their physical condition in learning so that the results of learning mathematics are optimal.Abstrak. Pandemi covid-19 yang telah menyebar di seluruh dunia pada awal tahun 2020 memberikan dampak dalam  kegiatan belajar mengajar di sekolah. Kementerian Pendidikan dan Kebudayaan serta beberapa pejabat daerah  mengeluarkan kebijakan berupa merubah kegiatan belajar mengajar dilaksanakan secara daring (online ). Penelitian ini bertujuan untuk mengetahui seberapa besar faktor yang mempengaruhi berpikir kritis matematika siswa dalam  proses pembelajaran secara daring  selama masa pandemi covid-19 dan untuk mengetahui faktor yang signifikan mempengaruhi berpikir kritis siswa yang totalnya ada 20 pernyataan. Populasi dalam penelitian ini adalah siwsa SMA di Gg.Tabib Jl.Bunga Kardiol Ladang Bambu dan jumlah sampelnya 29 siswa. Instrumen dalam penelitian ini berupa angket atau kuisioner.Hasil penelitian ini memperoleh bahwa analisis faktor berpikir kritis matematika siswa dalam proses pembelajaran secara daring selama masa pandemi covid-19 berpengaruh positif. Pada uji reliabilitas , kondisi fisik memiliki nilai 0.679% ,artinya indikator kondisi fisik mempengaruhi berpikir kritis sebesar 67.9% dan kecemasan memiliki nilai sebesar 0.675%, artinya indikator kecemasan mempengaruhi berpikir krtis. Sehingga dapat disimpulkan bahwa faktor yang mempengaruhi berpikir kritis belajar matematika siswa adalah faktor yang memiliki nilai tertinggi adalah faktor kondisi fisik. Maka perlulah para siswa untuk terus menjaga kondisi fisik mereka dalam belajar sehingga hasil belajar matematika optimal.